2001
DOI: 10.1073/pnas.101130398
|View full text |Cite
|
Sign up to set email alerts
|

Identification of multiple quantitative trait loci linked to prion disease incubation period in mice

Abstract: Polymorphisms in the prion protein gene are known to affect prion disease incubation times and susceptibility in humans and mice. However, studies with inbred lines of mice show that large differences in incubation times occur even with the same amino acid sequence of the prion protein, suggesting that other genes may contribute to the observed variation. To identify these loci we analyzed 1,009 animals from an F2 intercross between two strains of mice, CAST͞Ei and NZW͞OlaHSd, with significantly different incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
154
1
2

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 172 publications
(164 citation statements)
references
References 38 publications
7
154
1
2
Order By: Relevance
“…Studies using model systems have also suggested that hostencoded factors other than PrP C may be required to propagate prions in vitro and in vivo (5)(6)(7)(8)(9)(10). Furthermore, the restricted range of neuronal and nonneuronal cell types that are susceptible to infection by prions also suggests the existence of prion propagation cofactors (11)(12)(13).…”
mentioning
confidence: 99%
“…Studies using model systems have also suggested that hostencoded factors other than PrP C may be required to propagate prions in vitro and in vivo (5)(6)(7)(8)(9)(10). Furthermore, the restricted range of neuronal and nonneuronal cell types that are susceptible to infection by prions also suggests the existence of prion propagation cofactors (11)(12)(13).…”
mentioning
confidence: 99%
“…Careful phenotype comparison confirmed the presence of two distinct mouse strains, one resembling the Chandler strain, the other the mouse BSE strain [5,125]. This was an important observation since it suggests that other loci than PrP might influence not only the susceptibility [124,136] but also the strain evolution. Puzzlingly, however, these results have not been reproduced in another study using a similar panel of inbred mice and different BSE isolates [45].…”
mentioning
confidence: 68%
“…Mice were anesthetized with isofluorane/ O 2 and inoculated intracerebrally into the right parietal lobe with 30 μL of a 1% prion-infected brain homogenate as previously described (13). Mice were examined daily for neurological signs of prion disease and were culled once a definitive diagnosis had been made or earlier if showing signs of distress.…”
Section: Discussionmentioning
confidence: 99%
“…In mice, this is exemplified by the comparison of incubation times from a range of Prnp a inbred lines showing a difference of over 100 d between the shortest and longest incubation time strains (11). Many approaches have been taken to identify susceptibility genes including a genome-wide association study (GWAS) for variant CJD (vCJD) (6), and in mice, several studies have carried out quantitative trait loci mapping in both twoway crosses and a heterogeneous cross (12)(13)(14). In these studies, the underlying functional polymorphism is unknown but could be an amino acid change within the coding region of a protein or splicing variant or may occur within noncoding sequences such as untranslated regions, promoters, or other regulatory regions thereby influencing the pattern or level of expression.…”
mentioning
confidence: 99%